METODE BERMAIN PERAN UNTUK PENANAMAN PENDIDIKAN NILAI SPIRITUAL - M Imam (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
This research was aimed at examining the role-playing method for value education focusing on the values of honesty, patience, and obedience in religious worship, and in learning of Indonesian language . This research use descriptif qualitatif analysis and it was done is SMP Negeri 1 Turi,Lamongan.The subject of this research was the students of SMP Negeri 1 Turi grade 8.They are consist of 33 students.The data of this research was collected by analysing the result of pre test and post test marks. Based on the results of this research we can conclud that: (1)The increasement on the value of honesty on the students after tought by using role playing method was high,this can be seen on the prosentation result of pre test and post test ,10,4%. (2)The increasement on the value of patience on the students after tought by using role playing method was high,this can be seen on the prosentation result of pre test and post test ,17,5%. (3) The increasement on the value of obidience of religion worship on the students after tought by using role playing method was high,this can be seen on the prosentation result of pre test and post test ,19,0%. (4) The increasement on the value of listening on the students after tought by using role playing method was high,this can be seen on the prosentation result of pre test and post test ,10,0%. (5) The increasement on the value of speakingon the students after tought by using role playing method was high,this can be seen on the prosentation result of pre test and post test ,13,9% Based on these data we can conclude that the role playing method can be used to increase the value education in the proces of teaching Bahasa Indonesia for students.